2011
DOI: 10.1007/s13577-011-0024-1
|View full text |Cite
|
Sign up to set email alerts
|

Decreased motility of human spermatozoa presenting phosphatidylserine membrane translocation-cells selection with the swim-up technique

Abstract: Phosphatidylserine membrane translocation (PST) is considered to be a marker of apoptosis; however, numerous studies have reported on its role in processes not related to cell death. The purpose of the study was to investigate: (1) what is the impact of PST on the motility of spermatozoa, and (2) does the swim-up isolation involve the percentage of cells presenting PST? Semen of 28 normozoospermic men (WHO criteria) was analyzed. High motility spermatozoa were isolated by the swim-up technique. The percentage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In this investigation, PS(40:2) was found significantly decreased in infertile patients ( Figure 5 ). PS are known to be involved in apoptotic cell events through the process of PS membrane translocation, which is recognized as an important biological event in the cell ( Kotwicka et al, 2013 ). It was suggested that PS membrane translocation could be responsible for the changes in the spermatozoa cell membrane which happen during capacitation and acrosome reaction or during the elimination of pathological spermatozoa ( Kotwicka et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this investigation, PS(40:2) was found significantly decreased in infertile patients ( Figure 5 ). PS are known to be involved in apoptotic cell events through the process of PS membrane translocation, which is recognized as an important biological event in the cell ( Kotwicka et al, 2013 ). It was suggested that PS membrane translocation could be responsible for the changes in the spermatozoa cell membrane which happen during capacitation and acrosome reaction or during the elimination of pathological spermatozoa ( Kotwicka et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…OEC would also be able to discriminate between annexin negative spermatozoa, with their morphologically superior quality, and annexin positive sperm. 58 Moreover, PS translocation is associated with a decrease in the adenosine triphosphate (ATP) level of spermatozoa 59 and with a lower mitochondrial potential, 60 and so the OECs do not bind these spermatozoa because they have insufficient energy reserves to remain in the sperm reservoir and perform fertilization. Another explanation is that phospholipids (including PS) are incorporated into the sperm membrane by OEC 61 as a selection mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In such a context, our observation about positive correlation between sperm apoptotic markers and the fertilization rate of conventional IVF appears well grounded. The midpiece location of the PST and activation of caspase-3 suggest mitochondrial dysfunction, both by the location itself and by decreased sperm motility [ 20 ] resulting in impaired fertility potential. Nevertheless, the active caspase-3 presence does not represent a decisive indicator for cell death as the time of spermatozoa vital time was showed not to increase after incubation with caspases inhibitors [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher PST was found in men with lower sperm quality than sperm donors [ 17 19 ]. The presence of PST is related to lower vitality and motility of the sperm cells [ 20 ]. In contrast, Ricci et al [ 21 ] did not find correlation between PST and sperm parameters [ 21 ].…”
Section: Introductionmentioning
confidence: 99%